2023
DOI: 10.59717/j.xinn-med.2023.100023
|View full text |Cite
|
Sign up to set email alerts
|

Confinement-guided ultrasensitive optical assay with artificial intelligence for disease diagnostics

Wenjing Zhang,
Yongfeng Lu,
Chenyi Su
et al.

Abstract: <p>The necessity for ultrasensitive detection is becoming increasingly apparent as it plays a pivotal role in disease early diagnostics and health management, particularly when it comes to detecting and monitoring low-abundance biomarkers or precious samples with tiny volumes. In many disease cases, such as cancer, infectious disease, autoimmune disorder, and neurodegenerative disease, low-abundant target biomarkers like circulating tumor cells (CTCs), extracellular vesicle (EV) subpopulations, and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…According to the related studies shown in the CEPC CDR, a BMR of better than 4% can meet most requirements for Higgs measurements, but the further improvement of the BMR is still necessary for the flavor and new physics measurements. Benefiting from the continuous development of novel materials [13] and photoelectric detection [14,15], a conceptual design of high-granularity glass scintillator hadronic calorimeter (GSHCAL) based on particle flow paradigm has been proposed recently and can achieve a BMR of around 3.38% with an initial parameter configuration [16], which shows great potential to improve the BMR significantly. However, this initial configuration in the conceptual design is a relatively ideal scheme, which still need more optimization to balance the key physics performance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…According to the related studies shown in the CEPC CDR, a BMR of better than 4% can meet most requirements for Higgs measurements, but the further improvement of the BMR is still necessary for the flavor and new physics measurements. Benefiting from the continuous development of novel materials [13] and photoelectric detection [14,15], a conceptual design of high-granularity glass scintillator hadronic calorimeter (GSHCAL) based on particle flow paradigm has been proposed recently and can achieve a BMR of around 3.38% with an initial parameter configuration [16], which shows great potential to improve the BMR significantly. However, this initial configuration in the conceptual design is a relatively ideal scheme, which still need more optimization to balance the key physics performance (i.e.…”
Section: Introductionmentioning
confidence: 99%